Proyecto de factibilidad para la implementación de un taller de mecánica Automotriz en la ciudad de Loja. - Minga Gaona, Jaime Enrique (2012)
The next project "PROJECT FEASIBILITY FOR THE IMPLEMENTATION OF AUTOMOTIVE MECHANICS WORKSHOP CITY OF LOJA", aims to analyze the convenience of improvements to an existing service in this city and expand its field of activity, such as adding new services to vehicle fleet using technology to its competition. To achieve the above provides the information needed to accept or reject this project in accordance with the results obtained from the analysis of the factors that affect its operation. This analysis includes the following aspects: market / commercial. Technical, administrative and financial, concluding with an assessment of business on the terms proposed by quantifying the relationship Benefit - Cost and sensitivity analysis for different options. The most important contents of the Project that are taken into account as structured as follows: in the first phase we have a study at the automotive market all the results obtained tabulations surveys conducted both for customers who own vehicles as well for the owners own garages competition the same as it made with the sample of 934 surveys, here also is a marketing plan which refers services portfolio company as well as physical infrastructure, price service to be provided, the square or place marketing and advertising communication. Then we have the technical aspects which show the size of the company's capacity utilization. In the case of CAR CENTER (our company) forecast 50% work for the first year because it is a new workshop and unknown, for the second year is expected to work at 75% capacity and the third to 100% within this study also emphasizes the location macro, micro location and the description of tools and equipment. While the study refers to administrative business structure, hierarchical levels, philosophical foundation of the company and manual functions. Within the financial study is a sized budget. We get the state income, breakeven, NPV cash flow (which corresponds to the estimated value of income and expenses to be used in all and each of the years of economic operation of the project in this case our NPV of the project 734144,69), benefit cost allows to measure the performance you get for each dollar amount invested, to decide whether the project is accepted or not based on: If the ratio is greater than 1 the project is profitable and the result of our project can be overcome to 1 2.32 which is favorable, we also have the IRR, payback period of capital (which allows the time to know be recovered the inversion initial. in this case the time to recover our investment capital will be in 6 years, 6 months and 25 days) and at the end of this study is the sensitivity analysis (not only the degree of elasticity profitability the project). Finally, there is disclosed the conclusions and recommendations of the investment project.